PENGAMBILAN KEPUTUSAN HUTANG PADA USAHA KECIL DAN MENENGAH (UKM) DI PULAU LOMBOK: SUATU PERSPEKTIF BEHAVIORAL FINANCE - Siti Aisyah Hidayati; Embun Suryani; M Muhdin (Master of Management, Mataram University, 2019)
The purpose of this study is to find out what factors determine decision making of debt and what are the most dominant factors in decision making of debt for SMEs on the island of Lombok. This research is an explanatory research with quantitative approach. The population is all SMEs located in Lombok island. The sample is selected by Non probability sampling technique with a judgment sampling method where the SMEs that selected as samples are SMEs in handicraft industry of pottery and already exporting the products. Of the existing population, there are 25 (twenty five) SMEs that can be sampled. Respondents in this study are managers who also the owner of the SMEs. Data was collected using questionnaire. To achieve the research objectives, the data obtained will be processed according to needs using Factor Analysis.The results of this study indicate there are three groups of factors that determine decision making of debt, namely the First Factor Group consists of: Variable Excessive Optimism, Variable Overconfidence, Variable Confirmation Bias and Variable Aversion to sure loss. This factor is named Factor Overconfidence. The Second Factor Group consisted of Representativeness Variables, Avaibility Variables and Anchoring and Adjustment Variables. This factor is named the Avaibility Factor. The third factor group consists of Affect Variables and Aversion Loss Variables. This factor is named the Factor of Loss Aversion. The most dominant factor in determining debt decision making for SMEs in Lombok Island is the Overconfidence factor group consisting of Variable Excessive Optimism, Variable Overconfidence, Variable Confirmation Bias and Variable Aversion to sure loss .Keyword:Behavioral finance, decision making of debt, SMEs